La formación de los valores ecológicos y sus incidencias en el comportamiento social de las niñas y niños de primer año de educación básica de la escuela Filomena Rojas de la ciudad de Loja en el periodo 2012- 2013 - Tacuri Castillo, Paola Marisol (2015)
It is essential that the children, from a very young learn to respect and appreciate nature. Therefore, that arose this subject of research. THE TRAINING OF THE VALUES ECOLOGICAL AND YOUR INCIDENTS IN BEHAVIOR SOCIAL OF THE CHILDREN OF FIRST YEAR OF BASIC EDUCATION OF THE SCHOOL "FILOMENA ROJAS" FROM LOJA CITY IN THE PERIOD 2012-2013 General objective to determine the impact of the ecological values and their influence on the social behavior of children of the first year of basic education of the school "Filomena Rojas" from Loja city in addition that for the development of the same applies to the following methods: scientific method, scientific observation, deductive method, historical method, logical, descriptive method. Instruments used in the analysis and interpretation of data we find large percentage comprised that in the surveys the teachers it was determined that 100% of.